Urban Development Policy Challenges in East-Central Europe: Governance, City Regions and Financialisation - Buček, Ján (Quaestiones Geographicae, 2016)
This paper responds primarily to current innovations that have emerged in urban development policy during the last decades also in East-Central Europe. Prior to the change of the social regime, we notice more traditional approaches in the urban development policy - public consumption, economic development and environmental issues. Among current urban development challenges in this region we may focus on governance, city regions, and financialisation. Besides an outline of a general framework, their application is studied in the case of Bratislava. We argue that especially economic development and environmental issues were neglected in the urban development policy during the socialist period. More elementary development issues obtained priority as policy positions during the early transition period. Taking up more current challenges was delayed compared with western cities, and they have specific features. Nevertheless, it seems that cities in this region recognised the importance of the mutually multiplying effects of governance, city regionalism and financialisation in an urban development policy.